Interior spaces which cause anxiety among Filipino youth - Diño, Reynier Loislane R.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT Interior designers have the responsibility to create spaces which are beneficial to the well-being of the client. A well-being of a person does not only include physical well-being, but social and psychological well-being as well. To cater to the psychological needs of a person, the study aimed to determine the reasons why certain interior spaces cause anxiety. This study relied on the cultural aspects which affect a person's perception of space and did not consider the psychological conditions of respondents such as phobias and disorders. This is a qualitative study in which focus group discussions were conducted and a grounded theory approach was used in analyzing the data. The population of this study was composed of the Filipino youth, ages of 15 to 30 years old. Purposive sampling method was used to determine the respondents of the study. There was a total of 18 respondents grouped into three age brackets namely Bracket A (15 to 20 years old), Bracket B (21 to 25 years old), and Bracket C (26 to 30 years old). Each age bracket had a focus group discussion and all groups followed the same discussion guide. The findings of the study have proven that certain physical features of the space affected the perceived quality of the space which can trigger anxiety. According to the perceptions of the respondents, the observed characteristics of spaces which cause anxiety were dark, dead, abandoned, empty, enclosed, trapped or tight spaces. These attributes were associated to certain meanings in the Filipino culture and therefore being able to determine which spaces cause anxiety. Also, the reactions towards the spaces were explained through the elements of the Filipino culture namely beliefs, values, norms, sanctions, language, technology, and material culture. It was proven that culture and external factors, such as experiences and history, influence the perception of space.
Thesis (BS Interior Design)--University of the Philippines Diliman.
Keywords: Space -- Psychological aspects